Analysing prognostic factors among patients with perforative peritonitis - Wagh, Pradeep M.; Patil, Samadhan (International Surgery Journal, 2021)
Background: The mortality of perforation peritonitis is highly dependent on early approach to the hospital, quick diagnosis and prompt surgical treatment as it correlates with the duration and degree of peritoneal contamination, the patient's age, the general health of the patient and the nature of the underlying aetiology. The present study was done to assess the role of various prognostic factors which have a bearing on the final outcome of the patients. Methods: This prospective observational cross-sectional study was conducted in the at a tertiary level hospital in Maharashtra, in which 47 patients who presented a surgical emergency of perforation peritonitis and underwent an exploratory laparotomy were included. We compared different variables between patients who survived and those who died. Results: High mortality was also found in patients who presented after 24 hours of developing symptoms. Ileal perforation was significantly more common among dead patients (50%) as compared to patients who survived (20%), p-value<0.05. There were significantly higher proportion of patients who had shock on day 1 who died (67%) as compared to those who survived (12%), p-value<0.05. Also, the group of patients who died, had significantly higher MPI (p-value<0.01), higher proportion of patients with multiple perforations (p-value<0.05), larger perforations (p-value<0.01) and contamination more than 1000 ml (p-value<0.05). Conclusions: High mortality was observed in patients who presented late, had ileal perforations, multiple and large perforation and developed shock on day one.